Scirrhous hepatocellular carcinoma: systematic review and pooled data analysis of clinical, radiological, and histopathological features - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Schulz, Erik R.; Sterkenburg, Anthe; Mayer, Philipp; Pfeiffenberger, Jan; Hoffmann, Katrin (Journal of hepatocellular carcinoma, 2021)
Examining data on the clinical, radiological, and histopathological features of scirrhous hepatocellular carcinoma to guide further research into subtypes.
Gesehen am 24.11.2021